Communication challenges between nurses and migrant paediatric patients. (May 2020) - Kaufmann, Beatrice; Helfer, Tannys; Pedemonte, Dana; Simon, Marika; Colvin, Sarah
Background: Many people receiving medical treatment in Switzerland speak none of the country's four languages or English, which is a major communicative barrier for health staff. Appropriate treatment in hospitals depends on the successful communication between hospital staff and patients. Consequently, migrant patients can be particularly challenging for hospital staff. Aims: The aim of this project was to examine the following topics: (a) which communicative challenges hospital nurses are confronted with in the care of migrant paediatric patients and how they cope with them, and (b) what requirements nurses (and other stakeholders) have regarding a digital communication aid to improve the care of migrant paediatric patients in the hospital setting. Methods: This study used a qualitative approach. The following steps of data collection were undertaken: (a) two literature searches corresponding to the research questions, (b) a focus group interview with paediatric hospital nurses, (c) observation of communication between paediatric nurses/healthcare professionals and children/parents through shadowing, (d) short interviews with paediatric nurses who were being shadowed, and (e) a focus group interview with experts. Data analysis was based on thematic analysis and was supported by MAXQDA software. Results: Evaluation of the data showed there are multiple communicative challenges that emerge in the care of migrant paediatric patients. These challenges influence each other and appear at different moments in the hospital stay. Additionally, the results revealed that digital communication aids must be user friendly and easily accessible. Conclusions: This study highlights the areas of hospital care in which a digital communication aid could be feasible. However, many of the described communication challenges stem from issues that cannot be solved solely with a digital communication aid. Instead, strategies to tackle these issues must be embedded in the training of nursing staff, in the hospital management strategy and at the political level.